2017
DOI: 10.5336/nurses.2016-51005
|View full text |Cite
|
Sign up to set email alerts
|

What are the Trues in Applicating of Intramuscular Injection to Children?: Review

Abstract: Ö ÖZ ZE ET T Hemşirelik uygulamalarında intramusküler enjeksiyon, kolay bir beceri olarak düşünülmesine karşın güvenli ve uygun şekilde yapılmadığında çok ciddi komplikasyonlara yol açabilmektedir. Rahatlatma teknikleri, pozisyonu, ilaç miktarı, bölgenin seçimi ve çocukların kas kütlesi miktarı her intramusküler enjeksiyondan önce değerlendirilmeli, çocuğun yaşı ve gelişimine göre belirlenmelidir. Enjeksiyon bölgesi olarak yenidoğan ve küçük çocuklarda (<3 yaş) vastus lateralis, üç yaş ve daha büyük çocuklarda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…1,18 Nurses who deliver IM injection are responsible for administering the right drug to the right patient at the correct dose at the right time via appropriate route and register all the details. 1,2,4,5,7 The literature shows that VG site can be safely used for IM injection since it does not have large blood vessels or nerves and it is away from bone tissue. 4,22 Even though VG site is described as the safest site for IM injection, majority of the nurses prefer DG site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,18 Nurses who deliver IM injection are responsible for administering the right drug to the right patient at the correct dose at the right time via appropriate route and register all the details. 1,2,4,5,7 The literature shows that VG site can be safely used for IM injection since it does not have large blood vessels or nerves and it is away from bone tissue. 4,22 Even though VG site is described as the safest site for IM injection, majority of the nurses prefer DG site.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is not possible for nurses to identify the site in children by using their own hands. 5,24 The study by Wynaden et al revealed that determining VG site, small area for injection which may necessitate the use of other sites for patients requiring repeated injections and determing anatomically it for this reason, nurses prefer DG site. 24 Strohfus et al state that it is more challenging for nurses with inexperience and newstarters to spot and use VG site.…”
Section: Nurses' Features Of Im Injection Administrationmentioning
confidence: 99%
See 2 more Smart Citations